2022
DOI: 10.7717/peerj.14086
|View full text |Cite
|
Sign up to set email alerts
|

Ac2-26 attenuates hepatic ischemia-reperfusion injury in mice via regulating IL-22/IL-22R1/STAT3 signaling

Abstract: Hepatic ischemia-reperfusion injury (HIRI) is one of the major sources of mortality and morbidity associated with hepatic surgery. Ac2-26, a short peptide of Annexin A1 protein, has been proved to have a protective effect against IRI. However, whether it exerts a protective effect on HIRI has not been reported. The HIRI mice model and the oxidative damage model of H2O2-induced AML12 cells were established to investigate whether Ac2-26 could alleviate HIRI by regulating the activation of IL-22/IL-22R1/STAT3 sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Wanzhen Li found that Ac2-26, a derivative of the endogenous inflammatory inhibitor Annexin A1 (AnxA1), can inhibit hepatocyte apoptosis induced by the mitochondrial pathway through activation of the IL-22/STAT3 pathway. Ac2-26 can also protect ATP and the mitochondrial membrane potential (MMP), inhibit MDA and ROS production, thus reducing IRI ( 65 , 66 ). Nicolas Melin found that the TLR5 agonist CBLB502 can attenuate hepatic IRI by binding to the TLR5 receptor and stimulating IL-22 production by affecting the different immune cells through activation of STAT3 ( 67 ).…”
Section: Stat3 and Upstream Inflammatory Cytokinesmentioning
confidence: 99%
“…Wanzhen Li found that Ac2-26, a derivative of the endogenous inflammatory inhibitor Annexin A1 (AnxA1), can inhibit hepatocyte apoptosis induced by the mitochondrial pathway through activation of the IL-22/STAT3 pathway. Ac2-26 can also protect ATP and the mitochondrial membrane potential (MMP), inhibit MDA and ROS production, thus reducing IRI ( 65 , 66 ). Nicolas Melin found that the TLR5 agonist CBLB502 can attenuate hepatic IRI by binding to the TLR5 receptor and stimulating IL-22 production by affecting the different immune cells through activation of STAT3 ( 67 ).…”
Section: Stat3 and Upstream Inflammatory Cytokinesmentioning
confidence: 99%